The Effectiveness and Safety of Transurethral (Bipolar) Plasmakinetic Resection of Prostate Combined with Thulium Laser for Large Benign Prostatic Hyperplasia (>80ml) - Xie, Tiancheng; Lai, Peng; Luo, Ming; Xu, Yunfei (Urology Journal, 2016)
Purpose: To evaluate the clinical curative effect and safety of transurethral (bipolar) plasmakinetic resection of theprostate (PKRP) combined with thulium laser in the treatment of large prostates (> 80mL). Materials and Methods: From January 2014 to December 2015, 61 patients with benign prostate hyperplasia(BPH) were treated with PKRP combined with thulium laser (n = 25) or PKRP only (n = 36). We retrospectivelyanalyzed the perioperative status of patients status during 3-month follow-up. Results: There was no significant difference between the two groups before treatment (P > .05). PKRP combinedwith thulium laser was significantly superior to PKRP in terms of surgical duration, intraoperative blood loss,postoperative bladder washing time, postoperative complications and time of hospital stay (P < .05). There were nosignificant improvements at international prostatic symptom score (IPSS), quality of life (QOL), maximum flowrate (Qmax), and post-void residual (PVR) urine between two groups after 3 months (P > .05). Conclusion: PKRP combined with thulium laser is superior than PKRP only for better surgical duration, lessbleeding, higher efficiency and much quicker recovery. It may be a better choice for the treatment of BPH withlarge prostate (> 80mL).